Critical success factors of information source on international student decision to study abroad / Nor Azah Jahari and Sabariah Yaakub - Jahari, Nor Azah; Yaakub, Sabariah (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Having the right and correct information is important in making a decision, especially for students who decide to study abroad. The information received by the student will affect their final decision. To figure out which country and institution to choose, international students will look at numerous information sources before making their final decision. The purpose of the study is to examine the critical success factors of information sources on international students who decided to study abroad. The pilot study sample consists of 31 respondents from 50 questionnaires distributed, with an average response rate of 62 per cent. The result of descriptive analysis reveals that the internal source of information is the major critical success factor in influencing international student to study abroad. Understanding the critical success factors is crucial for the future of the higher education market. Improving the information source, such as the internal information of the institution through the institution website, can assist higher education institutions in increasing international student enrolment.